DEVELOPMENT OF THE LIBRARIANSHIP: ANALYSIS OF THE STATUS OF LIBRARIAN PERSONNEL TRAINING IN UZBEKISTAN - Ganieva, Barno (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The paper aims to discuss the development of library science in Uzbekistan and the analysis of the current state of training in the field of librarianship. Training in the library sector has always been actual, since libraries are an integral part of the continuing education of the republic. The article provides an analytical overview of the development of the industry interconnected with human resources. The urgency of the problem lies primarily in the fact that it is aimed at substantiating a new approach to the study of the training and professional development of library specialists. The problem of training library workers needs to be developed, both methodological and theoretical foundations. At the same time, the development of a private scientific methodology in the library profession, including in the history and theory of training and professionalization of librarians, allows us to outline the framework for further scientific research.